Dynamic Verbs in Peaky Blinders Season 1 - Kushariputri, Nailla Shahifah Rahmadiva; Alam, Beny; Hadi, Imron (Jurnal Bahasa Asing, 2024)
The need to be able to understand what other people convey is very important for humans as social beings. Humans communicate through words that have forms and meanings that contain ideas, intentions, or emotions. This research was written to find out the meaning in the form of an action of a word form, namely a dynamic verb when it is associated with the whole sentence. Dynamic verbs and their types that will be analyzed are taken from the popular series, Peaky Blinders Season 1 Episode 1 and Episode 2. The writer took thirty data to be the object of the analysis. The qualitative method is the method used in the preparation of this study based on Saeed (2016) who divides dynamic verbs into four types namely, durative-punctual and telic-atelic as the main theory. The findings were: three data were declared as durative-atelic with a percentage of 10%, ten data were declared as punctual-telic with a percentage of 33.3%, and seventeen data were declared as durative-telic with a percentage of 56.7%. There are three positions from the findings, namely durative-telic as the most type, punctual-telic in the middle position, and durative-atelic as the least.